ANALISIS FAKTOR PENYEBAB TERJADINYA PERISTIWA MALAPETAKA 15 JANUARI (MALARI) 1974 - Aas Lailah; Iskandar Syah; Syaiful M (FKIP UNIVERSITAS LAMPUNG, 2013)
Abstract : Alaysis of Contributing to Disastrous Events in January 15, 1974. Based on the formulation, so that this study aimed for determining the all factors that cause the catastrophe event (Malari) in January 15, 1974 at terms of the political aspect. This study used the historical method with the literature’s and the documentation’s data collection techniques, while the data analysis is the qualitative data analysis. Based on the data that has been obtained, the results showed that the factors contributing to the catastrophe events (Malari) in January 15, 1974 for the political aspect is because 1) the existence competition of the government between Soemitro’s group and Ali Murtopo’s group. At the time of the Riots on January 15, 1974, the group Murtopo intentionally sent some people who are not being the students, while the Soemitro’s deliberately let the riots occurred and did not take a firm action. 2) The disclaimer for the foreign factories domination. The disclaimer is realized in a wide variety of exclamations. As in the form of criticism from some economists, several articles on the newspaper, discussions, and demonstrations which is undertaken by various groups, especially students.Keywords : Malari event, students, causes